Wood Extractives of Silver Fir and Their Antioxidant and Antifungal Properties - Viljem Vek (MDPI AG, 2021)
The chemical composition of extractives in the sapwood (SW), heartwood (HW), knotwood (KW), and branchwood (BW of silver fir (Abies alba Mill.) was analyzed, and their antifungal and antioxidant properties were studied. In addition, the variability of extractives content in a centripetal direction, i.e., from the periphery of the stem towards the pith, was investigated. The extracts were analyzed chemically with gravimetry, spectrophotometry, and chromatography. The antifungal and antioxidative properties of the extracts were evaluated by the agar well diffusion method and the diphenyl picrylhydrazyl radical scavenging method. Average amounts of hydrophilic extractives were higher in KW (up to 210.4 mg/g) and BW (148.6 mg/g) than in HW (34.1 mg/g) and SW (14.8 mg/g). Extractives identified included lignans (isolariciresinol, lariciresinol, secoisolariciresinol, pinoresinol, matairesinol) phenolic acids (homovanillic acid, coumaric acid, ferulic acid), and flavonoids epicatechin, taxifolin, quercetin). Secoisolariciresinol was confirmed to be the predominant compound in the KW (29.8 mg/g) and BW (37.6 mg/g) extracts. The largest amount of phenolic compounds was extracted from parts of knots (281.7 mg/g) embedded in the sapwood and from parts of branches (258.9 mg/g) adjacent to the stem. HW contained more lignans in its older sections. Hydrophilic extracts from knots and branches inhibited the growth of wood-decaying fungi and molds. KW and BW extracts were better free radical scavengers than HW extracts. The results of the biological activity tests suggest that the protective function of phenolic extracts in silver fir wood can also be explained by their antioxidative properties. The results of this study describe BW as a potential source of phenolic extractives in silver fir.